Tampilan Reproduksi Kambing Lokal Hasil Induksi Superovulasi dengan Ekstrak Pituitary Sapi (THE REPRODUCTIVE PERFORMANCE OF LOCAL DOES FOLLOWING INDUCED SUPEROVULATION WITH CATTLE PITUITARY EXTRACTS) - Siregar, Tongku Nizwan; Siregar, Indah Kesuma; Armansyah, Teuku; ., Syafruddin; Sayuti, Arman; ., Hamdani (Jurnal Veteriner, 2013)
The aim of this study was  to determine the effect of pituitary extracts on the reproductive threeperformance of local does. This study used 15 local female does that were divided into three treatmentgroups.  Each group consisted of five does.  All does were injected with 7.5 mg Prostaglandin F2? /PGF2?(Prostavet C, Virbac S.A) intramuscularlly, twice in 10 days interval. In group 1 (K1), the does wereinseminated 36 hours after last PGF2? administration.  In group II (KII), does were injected with 500 IUpregnant mare serum gonadotropine/PMSG (Folligon ™, Intervet, Boxmeer, Holland) on day 9 cycles andfollowed with injection of 7.5 mg PGF2? two days after. In group III (KIII), goats injected with pituitaryextract on days 9, 10, and 11 cycles with decreasing dose :  2, 1, and; 0.5 ml intramuscular injection locatedat some point, followed with injection of 7.5 mg PGF2? 2 days after. The does on the KII and KIII wereinseminated 36 hours after PGF2? administration. Parameters measured were oestrous percentage,pregnancy, kidding rate, twinning, total of litter size, and averages litter size.  Results showed that alldoes (100%) from all groups showed estrous and kidding rate. Percentage of pregnant does group I, II, andIII were  60, 40, and 80%, respectively. Percentage of twinning group I, II, and III were 0, 50, and 25%.  Thetotal of litter size group I and II were 3 does, and group III were 5 does. The averages litter size group I, II,and III were 1; 1.5; and 1.25 respectively. In conclusion, treatment with pituitary extracts can increasereproductive performance of local does.
Keywords: pituitary extracts, superovulation, local does, reproductive performance